Pelatihan Pengelolaan Google My Business pada Gudang Kelapa Do’a Ibu Tembilahan Indragiri Hilir - Bayu Fajar Susanto; Ahmad Ahmad; Indra Muchlis Adnan; Widyawati Widyawati; Raju Maulana; Andi Yusafri (STAI Auliaurrasyidin Tembilahan, 2022)
This community service activity aims to increase the number of quality entrepreneurs, cultivate reliable and superior entrepreneurial spirit, attitudes, behavior and abilities among the community, introduction to the current marketing process, introduction to the marketing process via Google My Business. The expected outputs after community service activities are: 1) increasing the number of quality orders, 2) realizing entrepreneurial ability and stability to produce quality products that consumers need, 3) optimizing existing marketing channels, 4) understanding the marketing process via Google My Business which can increase sales turnover which will have an impact on increasing profits. It is hoped that the Google My Business (Google My Business) material will make it easier for consumers to find Gudang Kelapa Doa Ibu so that product marketing has a wider reach and has an impact on increasing sales. The final result is expected, Gudang Kelapa Doa Ibu users can use the Google My Business application (Google My Business) as a marketing medium for their selling products. In the management of Google My Business (Google My Business), interesting, honest and trusted reviews will be a ranking factor that Google uses to display our business in search results. Therefore, we need to provide quality products and services so that we can get lots of good reviews. That way, our business opportunities appear at the top will be higher. Our positive response to these reviews, will increase the trust of customers.